Genre Emergence Developments in Print, TV and Digital Media - Brock, Alexander; Brock, Alexander (Peter Lang, 2019)
This volume presents a range of academic approaches to genre emergence which is representative of the currently ongoing research, while retaining a common methodological core. The articles presented here use methods from text linguistics, conversation analysis, literary studies and media linguistics. Different driving forces of genre emergence are identified, e.g. function, communication form and culture. This book also aims to cover the emergence of many different genres: It includes chapters on newspaper and magazine genres, readers' comments, print advertisements, TV news shows and sitcom series, Wutreden, shitstorms, weblogs and erotic romance novels.